Communicative approach to teaching foreign languages - Malika Salomova (Proceedings of The ICECRS, 2019)
Communicative language teaching is perhaps the most popular approach to foreign languages. It usually prioritizes fluency over accuracy and it is therefore vital to obtain and design study materials which will closely resemble real life communicative situations.